2022
DOI: 10.5772/intechopen.101582
|View full text |Cite
|
Sign up to set email alerts
|

Ruminal Microbiome Manipulation to Improve Fermentation Efficiency in Ruminants

Abstract: The rumen is an integrated dynamic microbial ecosystem composed of enormous populations of bacteria, protozoa, fungi, archaea, and bacteriophages. These microbes ferment feed organic matter consumed by ruminants to produce beneficial products such as microbial biomass and short-chain fatty acids, which form the major metabolic fuels for ruminants. The fermentation process also involves inefficient end product formation for both host animals and the environment, such as ammonia, methane, and carbon dioxide prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…Benchaar et al [ 39 ] reported that saponins have no effect on total protozoal populations or on generic composition. It is interesting to note that the antiprotozoal activity of saponins is only transitory [ 20 , 43 ]. The antiprotozoal effects of Sesbania sesban in sheep were observed [ 44 , 45 ].…”
Section: Saponins and Rumen Microbiota Populationmentioning
confidence: 99%
“…Benchaar et al [ 39 ] reported that saponins have no effect on total protozoal populations or on generic composition. It is interesting to note that the antiprotozoal activity of saponins is only transitory [ 20 , 43 ]. The antiprotozoal effects of Sesbania sesban in sheep were observed [ 44 , 45 ].…”
Section: Saponins and Rumen Microbiota Populationmentioning
confidence: 99%
“…The increase in OM intake and digestibility has been reported to result in high total VFA and acetate in lambs (Tadayon et al 2017 ). Feed organic matter is the main substrate for rumen microbial growth and VFA production (Faverdin 1999 ; Soltan and Patra 2021 ). However, Neto et al ( 2016 ) suggested that the acetate concentration is more related to NDF intake and digestibility.…”
Section: Discussionmentioning
confidence: 99%
“…Table (3) indicates that there were no significant differences (P> 0.05) in the pH of the rumen fluid and in the concentration of ammonia nitrogen after 24 hours of in vitro incubation. Table (3) showed that there was a significant superiority (p<0.05) in the metabolizable energy, total fatty acids and total gas in favor of the addition of 200, 300, 400 mg thymol compared to the control treatment (zero thymol). The value of metabolizable energy for the four treatments were 7.87, 10.50, 10.18, 10.59 MJ/kg dry matter respectively.…”
Section: Rumen Fermentation Propertiesmentioning
confidence: 92%
“…Rumen fermentation plays an important role in feed digestion and microbial production. However, microbial fermentation can lead to significant energy and protein losses through the production of methane and ammonia, which are environmental pollutants [3]. Therefore, rumen microbial fermentation can be diversified to improve productivity and mitigate adverse environmental effects.…”
Section: Introductionmentioning
confidence: 99%